Bacterial Profile and Antimicrobial Susceptibility of Isolates Recovered from Lower Respiratory Tract Infection for Patients in Rizgary Hospital, Erbil - Chawsheen, Mahmoud A.; Al-Naqshbandi, Ahmed A.; Abdulqader, Haval H. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2020)
Recognition of etiologies of lower respiratory tract infection (LRTI) may help in delivering effective treatment options and circumvent emergence of antibiotic resistance. This study was carried out to uncover bacterial profile and antibiotic sensitivity patterns among 310 LRTI patients attended Rizagary Hospital between January 2014 to December 2016. Standard laboratory techniques were applied in collecting, processing, and culturing sputum and bronchial wash specimens. VITEK® 2 compact systems were used to identify bacteria and their antibiotic sensitivity patterns. Results showed that Streptococcus parasanguinis and Acinetobacter baumannii were the most abundant gram-positive and gram-negative bacteria (GPB & GNB), respectively, isolated from sputum specimens. From bronchial wash specimens, only GNB were detected and Serratia marcescens was the most abundant one. Antibiotic sensitivity tests revealed that Streptococcus parasanguinis was the most resistant GPB and Acinetobacter baumannii was the most resistant GNB. Sputum recovered GPB were highly resistant to Ampicillin, Erythromycin, Levofloxacin, Trimethoprim/Sulfamethoxazole, and Tetracycline. Bronchial wash recovered GNB were highly resistant to Ampicillin, Minocycline, Pefloxacin, Piperacillin, and Ticarcillin. In conclusion, LRTIs are mainly associated with GNB rather than GPB. The recovered Streptococcus parasanguinis and Acinetobacter baumannii were found to be multidrug-resistant pathogens. Ampicillin was ineffective against any of recovered pathogenic bacteria.